Religion and national identities in an enlarged Europe - Spohn, Willfried; Koenig, Matthias; Knöbl, Wolfgang (Palgrave Macmillan UK, 2015)
Cover -- Half-Title -- Title -- Copyright -- Contents -- List of Figures -- Acknowledgments -- Notes on Contributors -- List of Abbreviations -- 1 Religion, Nationalism, and European Integration: Introduction -- 2 The (Fragile) Normalization of German Identity Within Europe -- 3 Changing Frameworks of National Identity in Post-communist Poland -- 4 Greek Identity and Europe: Entanglements and Tensions -- 5 Turkey in Europe, Europe in Turkey: History, Elites, and the Media -- 6 Religious Dimensions of National and European Identities: Evidence from Cross-national Survey Research
Gesehen am 17.06.2021
Description based upon print version of record
Keywords: Europa; Electronic books; Aufsatzsammlung; Nationalbewusstsein; Religiöse Identität; Europäische Integration